Synthesis, characterization, In silico, and In vitro studies of CuS–ZnO nanocomposite using mushroom extract - S. Anbazhagi; A. Murugesan; M. Paramanantham; K. Chinnaiah; Karthik Kannan; Nadezhda Palko; K. Gurushankar (Hybrid Advances)
The study aimed to evaluate the antimicrobial and cytotoxicity properties of CuS–ZnO nanocomposite via green synthesis method using mushroom extract as a reducing agent. These biological activities relationship of experimental data's were evaluated through the novel computational tool of In Silico approach. It is essential to identify thread of emerging diseases. The absorbance peak value of 251 nm in UV–Vis, and crystal planes (101), and (101) in XRD pattern was identified in the nanocomposite of CuS–ZnO. Metal oxide, metal sulfide and the reducing ability of biomolecules in the mushroom extract were analysed using FTIR spectroscopy. The spherical morphology was identified in SEM and HR-TEM analyses. Elemental composition in the EDAX analysis supported the resulted as a nanocomposite. The CuS–ZnO nanocomposite significantly exhibited antimicrobial activity against the pathogens of S. aureus (21 mm-zone of inhibition) and E.coli (25 mm-zone of inhibition). The cytotoxicity analysis shows a CuS–ZnO Nanoparticles have more cytotoxic effect in U87 cell lines. Clavilactone D could be more effective against fungal infections. Hence, this study explores the antimicrobial and Vitro studies green-synthesized CuS–ZnO nanocomposite and examined the responsible major biocompound for activity through the theoretical study. Hence, this work becomes potential for nanomedicine applications.